Program change analysis - Korel, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
Software maintenance involves making changes to a program to correct errors, to improve efficiency, or to extend the program functionality. For large programs, understanding the influence of program changes can be very aggravating. Program change analysis is a method of analyzing the differences between the original program and its modified version in order to determine the scope and effect of a modification.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka